Ultraviolet shielding composite particle, and cosmetic comprising the same
By coating ultraviolet shielding particles directly onto silica substrate particles, the composite particles address the issues of agglomeration, roughness, and environmental impact in traditional UV shielding cosmetics, achieving effective UV shielding and a smooth skin feel.
Patent Information
- Application Number
- JP2023178094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Existing cosmetics containing ultraviolet shielding particles like titanium oxide, zinc oxide, and cerium oxide face issues such as strong agglomeration, creaking, and roughness, while also contributing to environmental pollution due to petroleum-derived resin particles. Additionally, these particles are unstable in high-temperature water and do not provide a smooth skin feel.
The development of composite particles where ultraviolet shielding particles are directly coated onto the surface of silica substrate particles, which are environmentally friendly and reduce microplastic pollution. This composite structure improves dispersion in cosmetics, reduces unevenness in UV shielding, and provides a smooth skin feel.
The composite particles effectively shield ultraviolet rays in the 270-400 nm range, offering a smooth skin feel while reducing environmental impact. They can be well dispersed in cosmetic substrates without special treatment, addressing the issues of agglomeration and roughness associated with traditional UV shielding particles.
Smart Images

Figure 2025068298000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to composite particles and cosmetics containing the same, and more particularly to composite particles in which the surface of a base particle is directly coated with ultraviolet ray shielding particles, and cosmetics containing the same. [Background technology]
[0002] Various types of cosmetics containing powders have been known. These powders are selected and blended into cosmetics based on their intended purpose, such as properties such as spreadability, fit (adhesiveness), smoothness, hiding power, and ultraviolet ray shielding ability.
[0003] Titanium oxide, zinc oxide and cerium oxide are used as ultraviolet shielding particles, but when these particles are used alone, they have the disadvantage that they tend to aggregate strongly, causing a squeaky or rough feeling.
[0004] Patent Document 1 discloses composite particles in which titanium oxide having an average particle diameter of 179 nm is coated on resin particles such as nylon as ultraviolet ray shielding particles for wavelengths of 290 to 400 nm. However, the resin particles used in these composite particles are petroleum-derived resin particles, which are a material that is difficult to decompose in nature and are therefore undesirable from the viewpoint of environmental pollution.
[0005] Patent Document 2 discloses composite particles coated with starch instead of petroleum-derived resin particles, but starch has the problem of being unstable in high-temperature water.
[0006] Patent Document 3 discloses that in order to improve the ultraviolet shielding properties, first titanium oxide fine particles having a nearly spherical shape and an average particle diameter of 0.01 to 0.1 μm are mixed with second titanium oxide fine particles having a spindle-shaped particle shape with a minor axis of 0.005 to 0.02 μm and a major axis of 0.01 to 0.10 μm. It also discloses that when the spherical titanium oxide fine particles and the spindle-shaped titanium oxide are mixed in a specific ratio (3:1 to 1:9), the dispersion state of each titanium oxide fine particle is improved, and the SPF increases by up to about 6. However, even if the SPF can be improved, the problems of squeaking and roughness of the titanium oxide fine particles remain. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2013-221148 A [Patent Document 2] Patent Publication No. 2021-24789 [Patent Document 3] Japanese Patent Application Publication No. 7-165532 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, the objective of the present invention is to provide a cosmetic composition that reduces microplastics, which have been identified as a cause of environmental pollution, is stable even in high-temperature water environments, has excellent ultraviolet shielding properties, and feels smooth on the skin. [Means for solving the problem]
[0009] That is, the present invention relates to a composite particle having a base particle and an ultraviolet-shielding particle directly coated on the surface of the base particle, wherein the base particle includes silica and the ultraviolet-shielding particle includes one or more particles selected from titanium oxide, zinc oxide and cerium oxide.
[0010] Conventionally used spherical silica has a size of 4 to 20 μm and an apparent specific volume of 2 to 4 mL / g. The indicators used to gauge the feel are spreadability and softness. The larger the particle size, the better the spreadability, but when used in cosmetics, particles of 10 μm or less are generally preferred. If the particle size is more than 10 μm, the feel becomes lumpy. Softness is greatly influenced by the inherent properties of the material, and low-hardness resins such as nylon, cellulose, and silicone are excellent. Silica has high hardness, but the softness can be improved by increasing the apparent specific volume. The silica of the present invention is, for example, spherical, has a size of 4 to 10 μm, and an apparent specific volume of 4 to 8 mL / g. Effect of the Invention
[0011] The composite particles of the present invention effectively block ultraviolet rays in the wavelength range of 270 to 400 nm and give a smooth feel to the skin. Because silica is used as the base particle, it can reduce the burden on the global environment and contribute to the reduction of microplastics, which are considered to be one of the causes of environmental pollution. Furthermore, as a result of the composite particles being broken down into aggregates of the ultraviolet shielding particles, when the composite particles of the present invention are blended in a cosmetic material, they can be well dispersed in other cosmetic base materials and uneven ultraviolet shielding can be reduced.
[0012] For example, when ultraviolet shielding particles such as fine titanium oxide or fine zinc oxide are mixed alone without compounding to produce a cosmetic, the particles have strong cohesion and are difficult to disperse in other cosmetic base materials. For this reason, in the production of liquid foundation, inorganic particles including ultraviolet shielding particles may need to be dispersed using a three-roll mill or a bead mill. Similarly, in the production of powder foundation, dispersion treatment of crushing with a grinder or the like may be required.
[0013] Furthermore, these ultraviolet shielding particles tend to scatter, making handling, such as measuring, difficult, whereas the composite particles are in the form of granules, making handling easy. The composite particles produced by the present invention can be directly blended with other cosmetic base materials to produce cosmetics without any special dispersion treatment. [Brief description of the drawings]
[0014] [Figure 1] This is a scanning electron microscope (SEM) photograph of silica particles (apparent specific volume 5.4). [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of silica particles (apparent specific volume 6.7). [Diagram 3] This is a SEM photograph of composite particles in which the silica particles in Figure 1 are covered with 70% fine titanium dioxide. [Figure 4] This is a scanning electron microscope (SEM) photograph of composite particles in which the silica particles in Figure 1 are coated with 35% fine titanium dioxide and 35% fine zinc oxide. [Diagram 5] This is a scanning electron microscope (SEM) photograph of composite particles in which the silica particles in Figure 2 are coated with 70% of three types of titanium oxide (15nm60:35nm20:80nm20). [Figure 6] 1 shows the spectral transmittance when the composite particles of Examples 1 to 3 are dispersed in liquid paraffin at 3%. [Figure 7] 1 shows the spectral transmittance when the composite particles of Examples 1 to 3 are dispersed in liquid paraffin at 10%. [Figure 8] 1 shows the spectral transmittance when the composite particles of Examples 1 to 3 are dispersed in liquid paraffin at 20%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described, but the following invention is not limited to the specific embodiment.
[0016] The composite particle of the present invention is composed of a base particle and a plurality of ultraviolet shielding particles directly coated on the surface of the base particle.
[0017] (base material particles) The base particle is silica, for example, selected from hollow silica, porous silica, porous hollow silica, titanium oxide-containing silica, and the like. The larger the average particle size of the base material, the better the spreading characteristics, but there is a limit when it is blended into cosmetics. The average particle size is, for example, in the range of 3 to 100 μm, preferably 4 to 50 μm, and more preferably 4 to 20 μm. If the average particle size is less than 3 μm, spreading becomes poor and it becomes difficult to coat the ultraviolet shielding particles, and if it exceeds 50 μm, a rough feel is generated.
[0018] The apparent specific volume of the base particle may be in the range of, for example, 1 to 10 mL / g, preferably 2 to 8 mL / g, and more preferably 3 to 7 mL / g. If the apparent specific volume is less than 1 mL / g, the soft feel is lost and the hard characteristics of silica appear. If it is more than 8 mL / g, the silica becomes easily broken or floats loosely, making handling during production difficult. The shape of the base material particles is preferably spherical, but they may also be spherical or ellipsoidal, and the pore characteristics may be non-porous, porous, or hollow. The particle size distribution of the base particles is preferably normal, and the presence of extremely small particles, large particles or crushed particles is undesirable.
[0019] Silica is commercially available from Teika Corporation, JGC Catalysts and Chemicals, AGC Si-Tech Co., Ltd., Suzuki Oil Industries Co., Ltd., ABC Nanotech Co., Ltd., and the like. The surface of these silica particles may be subjected to a surface treatment such as water repellency treatment or hydrophilic treatment depending on the purpose of use, but there is no particular limitation.
[0020] (UV shielding particles) The ultraviolet ray shielding particles contain at least one selected from titanium oxide, zinc oxide, and cerium oxide. By changing the type and ratio of the ultraviolet ray shielding particles, the ultraviolet ray shielding effect can be selected. In the present invention, the ultraviolet ray shielding particles can be arbitrarily selected, which makes it easy to select from a wide variety of sunscreen cosmetics. The crystal structure of titanium oxide is classified into anatase type and rutile type, and the rutile type is preferable for cosmetic use.
[0021] When blocking ultraviolet rays in the B wave region of 270 to 320 nm, fine titanium dioxide with an average particle size of 15 to 25 nm is suitable. On the other hand, it transmits almost all visible light, so it does not cause a white cast when added to cosmetics.
[0022] When blocking ultraviolet rays in the B wave region of 270 to 380 nm and part of the A wave region, particles that are a blend of fine titanium oxide particles with an average particle size of 15 to 25 nm and fine zinc oxide particles with an average particle size of 20 to 25 nm are suitable. The ratio of the fine particle titanium oxide to the fine particle zinc oxide is 30-70:70-30, preferably 40-60:60-40, and more preferably 45-55:55:45. This is because fine particle zinc oxide blocks ultraviolet rays in the 320 to 370 nm range, whereas fine particle titanium oxide has a low blocking ability. It also transmits almost all visible light, so like fine titanium dioxide particles, it does not leave a white cast when added to cosmetics.
[0023] Furthermore, in the case of blocking ultraviolet rays in a wide range of 270 to 400 nm, particles in which fine particles of titanium oxide having different sizes are blended, with an average particle size of 25 to 80 nm, are suitable. Fine titanium dioxide particles with an average particle diameter of 15 to 25 nm are suitable for blocking UV rays in the 270 to 320 nm B wave range, fine titanium dioxide particles with an average particle diameter of 35 nm are suitable for blocking UV rays in the 340 to 350 nm B wave range, and fine titanium dioxide particles with an average particle diameter of 80 nm are suitable for blocking UV rays in the 350 to 400 nm wave range. The ratio of titanium oxides of different diameters is 15nm:35nm:80nm=40-80:40-10:40-10, preferably 15nm:35nm:80nm=50-70:30-20:30-20, and more preferably 15nm:35nm:80nm=55-65:25-15:25-15. On the other hand, since the transmittance of visible light of 400 nm or more is low, a whitish cast occurs, making it unsuitable for cosmetics that require transparency, such as sunscreens.
[0024] Fine particle titanium dioxide with an average particle size of 15 nm blocks ultraviolet rays in the range of 270 to 320 nm, but the blocking ability drops off rapidly in the range above that, so increasing the amount added cannot be expected to improve the SPF. In addition, composite particles made by blending fine titanium dioxide particles having an average particle diameter of 15 to 25 nm with fine zinc oxide particles having an average particle diameter of 20 to 25 nm are effective in blocking ultraviolet rays in the 270 to 380 nm B wave region and some of the A wave region, but it is difficult to block wavelengths higher than that. However, for example, composite particles using different sized particles of fine titanium dioxide have an inferior UV shielding ability at a low blending amount of, for example, 10% or less, compared to the above-mentioned single fine titanium dioxide or blend of fine titanium dioxide and fine zinc oxide. However, if the blending amount is increased to, for example, 20%, the UV shielding ability in the 270 to 350 nm wavelength region becomes the same, and by combining it with the original characteristic of the UV shielding ability in the 350 to 400 nm wavelength region, it becomes possible to achieve a high SPF. However, because it also blocks visible light, the transmittance of visible light is low and it causes a whitish cast, so it is not suitable for incorporation into skin care products. However, it is suitable for powder foundations and other products that require a high SPF.
[0025] As described above, one embodiment of the present invention uses fine titanium oxide particles having an average particle diameter of 15 to 25 nm as the base particles when blocking ultraviolet rays in the 270 to 320 nm range; when blocking ultraviolet rays in the 270 to 380 nm range, particles that are a blend of fine titanium oxide particles having an average particle diameter of 15 to 25 nm and fine zinc oxide particles having an average particle diameter of 20 to 25 nm; and when blocking ultraviolet rays in a wide range such as the 270 to 400 nm ultraviolet range, fine titanium oxide particles having sizes of 15 nm, 35 nm, and 80 nm are used as the base particles.
[0026] Fine particle titanium dioxide is commercially available from Croda Japan Co., Ltd., Teika Co., Ltd., Ishihara Sangyo Kaisha, Ltd., Titan Kogyo Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.
[0027] Fine particle zinc oxide is commercially available from Croda Japan Co., Ltd., Sakai Chemical Industry Co., Ltd., Teika Corporation, and the like.
[0028] The surfaces of these inorganic fine particles are subjected to a surface treatment such as a water repellent treatment or a hydrophilic treatment depending on the purpose of use, but there is no particular limitation.
[0029] (composite particles) One embodiment contains silica having an average particle size of 4 to 10 μm and an apparent specific volume of 3 to 8 mL / g as base particles, and the ultraviolet ray shielding particles can be selected depending on the ultraviolet ray wavelength to be shielded. For example, to block ultraviolet rays in the wavelength range from 270 to 320 nm, fine titanium oxide having an average particle size of 15 to 25 nm is used. For example, when blocking ultraviolet rays in the wavelength range of 270 to 380 nm, particles are used that are a blend of fine titanium oxide particles having an average particle size of 15 to 25 nm and fine zinc oxide particles having an average particle size of 20 to 25 nm. For example, when blocking ultraviolet rays in a wide range such as ultraviolet wavelengths from 280 to 400 nm, fine titanium oxide particles of 15 nm, 35 nm, and 80 nm are used.
[0030] The ratio of the ultraviolet shielding particles covering the silica is 30 to 90%, preferably 40 to 80%, and more preferably 50 to 70%. If the coverage is below 30%, there will not be enough particles to block UV rays, and sufficient UV blocking performance will not be obtained. Also, if it is over 80%, the UV particles that do not adhere to the silica surface will scatter and aggregate, making it difficult to disperse with other cosmetic base materials when manufacturing cosmetics, and impairing the smooth feel.
[0031] (Method of compounding) In the composite process, the fine particles are directly attached to the surface of the base particle by static electricity generated between the base particle and the fine particles due to frictional charging between the base particle and the ultraviolet shielding particle. Then, to make the attachment stronger, a physical force is forcibly applied from the outside by impact in a high-speed air stream. By such a process, the fine particles are firmly attached to the silica due to the interaction between the powders caused by friction or contact between the particles. In order to forcibly apply a physical force, the mixture can be produced using a mixer such as a jet mill, a hybridizer, a Henschel mixer, a Nauta mixer, a speed mixer, a V-type mixer, or a jet mill.
[0032] Details of this preferred method can be described with reference to the method described in Patent Document 2. That is, the above-mentioned adhesion step and the preferred strength improving step can be carried out using, for example, a Henschel mixer. Specifically, the base particles and the ultraviolet shielding particles are fed into a Henschel mixer, and the rotor is rotated at a low speed for a predetermined time to mix the base particles and the ultraviolet shielding particles, thereby carrying out the adhesion process. Subsequently, the rotor is operated at a high speed for a predetermined time to apply strong shearing forces and impact forces to the treated material, thereby causing the base particles and the ultraviolet shielding particles to adhere firmly to each other through interactions between the powders. The above-mentioned predetermined time varies depending on the amount of powder to be added, but for the adhesion process, it is, for example, 1 minute or more, especially 2 to 5 minutes. Even if it is 5 minutes or more, the adhesion state is good, but the cost efficiency of production is poor for a long time. For strength improvement, it is, for example, 10 minutes or more, especially 15 to 30 minutes. Even if it is 30 minutes or more, the strength improvement effect is obtained, but the cost efficiency of production is poor for a long time. As the treatment time passes, the compounding progresses, and the ultraviolet ray shielding particles become tightly coated on the surface of the silica. According to the above-mentioned method, the ultraviolet shielding particles can be coated on the base material particles without relying on the adhesive strength of other materials. Therefore, even if there is no organic material such as wax that encapsulates and integrates the ultraviolet shielding particles and the base material particles, the adhesion state between the base material particles and the ultraviolet shielding particles is maintained. In this embodiment, it is not necessary for the composite particles to contain an organic material that coats both the base material particles and the ultraviolet shielding particles and integrates them.
[0033] (Cosmetics) The composite particles of this embodiment are suitable for incorporation into cosmetics. The type of cosmetics containing the composite particles of this embodiment is not particularly limited, and can be incorporated into general cosmetics. For example, they can be incorporated into cosmetics such as foundation, face powder, base makeup, blusher, milky lotion, and cream. The amount of incorporation is not particularly limited, but is preferably 3 to 20%. Furthermore, the composite particles of the present invention are preferably blended into cosmetics for blocking ultraviolet rays, such as sunscreens and suncare foundations.
[0034] (Measurement of apparent specific volume) The measurement was performed in accordance with the apparent specific volume measurement method 1 (static method) of the general test method of the "Standards for Quasi-drug Ingredients 2021." For example, using an apparent specific volume measuring device (a sieve with 0.5 mm openings, a funnel, and a 30 mL container), the mass of the powder that passed through the upper sieve funnel in a 30 mL container is measured and calculated using the following formula. G=30 / F G: apparent specific volume (mL / g) F: Mass of treated sample in receiver (g) 30: Volume of receiver (mL)
[0035] (Observation of Complex Conditions) A scanning electron microscope JSM-6380LV manufactured by JEOL Ltd. was used.
[0036] (Measurement of average particle size) We used a laser diffraction particle size distribution analyzer, SYNC, manufactured by Microtrack Bell Co., Ltd. The average particle size was calculated by putting the powder into water, using a surfactant as a dispersant, irradiating it with ultrasound for 1 minute, and taking the volume-based 50% diameter (D50) value as the average particle size.
[0037] (Measurement of UV shielding ability) (Spectral transmittance measurement) The spectral transmittance was measured using a Shimadzu UV-3150 self-recording spectrophotometer. The composite particles produced in Examples 1 to 3 were thoroughly dispersed in liquid paraffin at 3%, 10%, and 20% to prepare samples. The composite particle / liquid paraffin dispersion thus prepared was filled into a quartz cell with a 0.1 mm recess. Then, using an integrating sphere of 60φ, the spectral transmittance was measured over the wavelength range of 270 to 700 nm.
[0038] 6, 7 and 8, the difference in the concentration of the composite particles in the liquid paraffin is clear depending on the type and combination of the ultraviolet ray shielding particles. The spectral transmittance at a composite particle concentration of 3% in liquid paraffin is lowest in the ultraviolet B wave range for Examples 1, 2, and 3, in that order, indicating excellent shielding ability. When the concentration of the composite particles in the liquid paraffin becomes 10%, the spectral transmittance in the UV-B and UV-A regions also tends to decrease in all of Examples 1, 2, and 3. Furthermore, when the concentration of the composite particles in the liquid paraffin becomes 20%, the spectral transmittance decreases in the order of Examples 3, 2, and 1, and then the order is reversed. In particular, the spectral transmittance of Example 3 is low for UV-A rays and over 400 nm, but the transmittance in the visible light region also tends to decrease, which causes a whitish cast. Although it can be used in foundations, it is not suitable for use in cosmetics that require transparency in visible light, such as skin care products. EXAMPLES
[0039] The present invention will be described in detail with reference to the following Production Examples, but the present invention is not limited to these Production Examples. The mass ratios of the components are in parts by weight and % by weight unless otherwise specified.
[0040] (composite particles) Example 1 30 parts of silica (ABC Corporation's "SILNOS160", average particle size 6 μm, apparent specific volume 5.4 mL / g) and 70 parts of titanium oxide (Teica Corporation's "MT100TV", average particle size 15 nm) were charged into a Henschel mixer. Inside the Henschel mixer, the mixture was rotated and mixed at a peripheral speed of 25 m / sec for 3 minutes to allow the titanium oxide to adhere to the surface of the silica, and then rotated at a peripheral speed of 88 m / sec for 10 minutes to form a composite. The Henschel mixer was then rotated at a peripheral speed of 20 m / sec or less, and the composite treated product was cooled to room temperature. By the composite, composite particles (15 nm fine particle titanium oxide 70%-silica composite) were obtained in which the titanium oxide fine particles were essentially coated on the surface of the silica particles (see Figure 3).
[0041] Example 2 Composite particles were obtained in the same manner as in Example 1, except that 35 parts of titanium oxide (manufactured by Teika, "MT100TV", average particle size 15 nm) and 35 parts of zinc oxide (manufactured by Sakai Chemical Industry, "FINEX50S-LP2") were used instead of 70 parts of titanium oxide (manufactured by Teika, "MT100TV", average particle size 15 nm) (see FIG. 4).
[0042] Example 3 Composite particles were obtained by treating in the same manner as in Example 1, except that 70 parts of titanium oxide (Teika's "MT100TV" average particle size 15 nm) were replaced with 42 parts of titanium oxide (Ishihara Sangyo Kaisha's "MPT186" average particle size 15 nm), 14 parts of titanium oxide (Ishihara Sangyo Kaisha's "TTO55C" average particle size 35 nm), and 14 parts of titanium oxide (Ishihara Sangyo Kaisha's "MPT142" average particle size 80 nm), and 30 parts of silica (ABC's "SILNOS160" average particle size 6 μm, apparent specific volume 5.4 mL / g) were replaced with 30 parts of silica (ABC's "SILNOS350" average particle size 9 μm, apparent specific volume 6.7 mL / g). (See FIG. 5)
[0043] (SPF measurement)
[0044] In addition to spectral transmittance, the SPF value is used as a characteristic of cosmetics to evaluate UV protection ability. Labsphere's SPF analyzer UV2000S is used to measure SPF (in vitro SPF), which measures the UV blocking ability over wavelengths of 270 to 400 nm and converts the UV blocking rate of each wavelength into a weighted numerical value.
[0045] The composite particles of Examples 1 to 3 were mixed in liquid paraffin at 3%, 10% and 20%, and thoroughly dispersed in a small mixer. This dispersion was uniformly applied to a plate (HELIOPLATE HD6) so that the coating amount was 1.3 mg / cm2 (32 to 33 mg / plate) to form a sample plate. The SPF was measured using an SPF analyzer, and the evaluation results are shown in Table 1.
[0046] [Table 1]
[0047] The SPF value is high in Example 1 and low in Example 3 when the blend amount is low, for example 3%, but the relationship is reversed when the blend amount is high, for example 20%. This tendency can be confirmed as a reversal phenomenon as is clear from the results of the spectral transmittance in Figs. 6, 7, and 8.
[0048] (Cosmetics) The composite particles of the present invention are suitable for incorporation into cosmetics. The type of cosmetics containing the composite particles of the present embodiment is not limited, and may be, for example, any of powder, powder solid, cream, milky liquid, lotion, oily solid, oily liquid, paste, etc. Examples of skin care cosmetics and makeup cosmetics, particularly cosmetics that are likely to exhibit the effects of the present invention, include foundation, face powder, blush, lipstick, sunscreen cosmetics, concealer, etc. (Examples 1 to 3, Comparative Examples 1 to 3) A powder foundation was prepared according to the formula shown in Table 2. Specifically, ingredients 1 to 13 were mixed and crushed, transferred to a high-speed blender, and then dissolved ingredients 14 to 19 were added and crushed uniformly. The mixture was press-molded into a medium-sized container to prepare the product. Foundation (%)
[0049] [Table 2]
[0050] The liquid foundation was prepared as shown in Table 3. Ingredients 1 to 16 (oil phase) and ingredients 17 to 21 (aqueous phase) are mixed together, and then the aqueous phase is added to the oil phase and emulsified. Liquid Foundation (%)
[0051] [Table 3] Powder foundation and liquid foundation were prepared using each of the composite powders obtained above, and sensory evaluations were carried out on the feel in use and cosmetic effect. For each of the cosmetic sensation evaluation items such as roughness, squeaking, and fit (adhesion), a test was conducted by 10 expert panelists, and the evaluation points were totaled based on the following evaluation criteria. The results are shown in Table 4.
[0052] [Table 4] Evaluation criteria 5 points; very good 4 points; excellent 3 points; average 2 points; poor 1 point; very poor Evaluation criteria ◎: Total score is 40 or more. ○: The total score is between 20 and 30. △: The total score is between 10 and 20 points. ×; The total score is less than 10 points.
[0053] It is evident from Examples 4 to 9 and Comparative Examples 1 to 6 that the cosmetics using the composite particles of the present invention have an excellent feel when in contact (applied) with the skin.
Claims
1. The composite particles are configured such that the surface of a base particle, which is silica having an average particle diameter of 4 to 20 μm and an apparent specific volume of 4 to 8 mL / g, is directly coated with ultraviolet-shielding particles, and the ultraviolet-shielding particles include one or more particles selected from titanium oxide, zinc oxide, and cerium oxide.
2. The composite particle according to claim 1 , wherein the coverage ratio of the ultraviolet ray shielding particles is 40% or more based on the total amount of the base particle and the ultraviolet ray shielding particles.
3. A cosmetic comprising the composite particle according to any one of claims 1 to 2.
Citation Information
Patent Citations
Cosmetic
JP1995165532A
Particulate ultraviolet ray absorbing material, and cosmetic product and resin composition compounded therewith
JP2013221148A
Composite particles and cosmetics containing the same
JP2021024789A